Characterization of compatibility of Polypropylene/Poly(butylene succinate) blends: Impact of weight ratios on interfacial polarization - Taktak, S.; Ghorbel, N.; Hammami, H.; Fakhfakh, S.; Rondot, S.; Jbara, O. (Journal of Molecular Liquids, 2022)
The main focus of the present work is the investigation of the aliphatic polyesters blend’s compatibility from the viewpoint of dielectric and structural properties. Polypropylene/poly(butylene succinate) (PP/PBS) polymer blends with different weight ratios were prepared using a twin-screw extruder and then a molded injection. The impact of blending PP and PBS on the molecular relaxation process and interfacial polarization of PBS was studied via broadband dielectric spectroscopy (BDS) over a large temperature domain varying between 20 °C and 100 °C and a frequency range from 0.1 Hz to 1 MHz. Three significant dielectric processes α-primary relaxation attributed to glass transition, and two interfacial polarizations due to the semi-crystalline character of PBS and the blended PP polymer are revealed and examined using the Havriliak-Negami (HN) fit. The most important point of the HN fit analysis is the study of the interaction of the dipoles trapped at the interfaces PP/PBS that allowed us to understand the state of the PP and PBS blend in terms of adhesion and compatibility. Atomic force microscope (AFM) and its electric mode electrostatic force microscopy (EFM) and differential scanning calorimetry (DSC) were performed as complementary techniques. AFM/EFM analysis and DSC thermograms confirm the poor compatibility and immiscibility between the two phases of the polymer blends (PP/ PBS).
Keywords: Compatibility; Dielectric spectroscopy; Interfaces; Interfacial adhesion; Polymer blends